The "Islamic Military Alliance": Between Combating Terrorism and Maintaining Saudi Security (2015-2017) - Diabat, Khier (Dirasat: Human and Social Sciences, 2019)
This study deals with the issue of "The Islamic Military Alliance" (IMA), which has been announced by the Kingdom of Saudi Arabia (henceforth KSA) on 15 December 2015, and has been linked to combating terrorism under the Saudi leadership. The study aims at explaining the impact of regional and international changes that affected the Saudi security perspective towards the establishment of this alliance - which includes 41 Arab and Islamic countries. The study also endeavors to explore the motives, objectives and interests that endorse the members especially KSA to join this kind of alliances. The study then attempts to analyze the nature of the security strategy adopted by IMA in achieving its objectives. The study sets out from the premise that there is a correlation between the growth of Saudi security needs and the maintenance of its security and national interests through the establishment of this alliance. To examine this hypothesis, the study poses a series of questions and has answered them. The study methodology is based on employing the historical, descriptive and analytical approaches to the research problem, objectives and questions to reach the research outcomes. Finally, the study concludes that KSA aims at achieving a range of national interests through this alliance besides the declared main goal on combating terrorism. The most important of these interests has been to balance the rise of Iranian power and restore the Saudi regional and international prestige in the region